2021
DOI: 10.1017/qua.2020.122
|View full text |Cite
|
Sign up to set email alerts
|

Using10Be dating to determine when the Cordilleran Ice Sheet stopped flowing over the Canadian Rocky Mountains

Abstract: During the last glacial maximum the Cordilleran and Laurentide ice sheets coalesced east of the Rocky Mountains and geomorphological evidence indicates ice flowed over the main ridge of the Rocky Mountains between ~54–56°N. However, this ice flow has thus far remained unconstrained in time. Here we use in situ produced cosmogenic 10Be dating to determine when Cordilleran ice stopped flowing over the mountain range. We dated eight samples from two sites: one on the western side (Mount Morfee) and one on the eas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 75 publications
2
5
0
Order By: Relevance
“…Initial separation of the CIS and LIS over the southern Mackenzie Mountains is not chronologically constrained, but further south (55°N), mountain summits over 2000 m asl became ice free as early as 15.6 ± 0.6 ka (Dulfer et al, 2021), consistent with our earliest ages on the deglaciation in the study area at Katherine Creek at 15.8 ka (17.1 -14 6 ka). The western margin of the LIS then stayed pressed against the eastern slopes of the Mackenzie Mountains during a period of ice sheet thinning between 14.9 and 14.3 ka (Fig.…”
Section: Opening Of the Ice-free Corridor And Faunal Migrationsupporting
confidence: 81%
See 2 more Smart Citations
“…Initial separation of the CIS and LIS over the southern Mackenzie Mountains is not chronologically constrained, but further south (55°N), mountain summits over 2000 m asl became ice free as early as 15.6 ± 0.6 ka (Dulfer et al, 2021), consistent with our earliest ages on the deglaciation in the study area at Katherine Creek at 15.8 ka (17.1 -14 6 ka). The western margin of the LIS then stayed pressed against the eastern slopes of the Mackenzie Mountains during a period of ice sheet thinning between 14.9 and 14.3 ka (Fig.…”
Section: Opening Of the Ice-free Corridor And Faunal Migrationsupporting
confidence: 81%
“…In addition, recent studies in adjacent regions of the LIS also included a GIA correction (Norris et al, 2022;Reyes et al, 2022) and hence, to ensure comparability with these datasets, we apply a correction for GIA related changes to our dataset as well. The previously mentioned changes in atmospheric conditions following deglaciation work against the impact of GIA on calculated exposure ages, but the impact on exposure ages is likely an order of magnitude lower than that of GIA induced impacts (Staiger et al, 2007;Cuzzone et al, 2016;Ullman et al, 2016;Dulfer et al, 2021).…”
Section: Exposure Age Calculationmentioning
confidence: 97%
See 1 more Smart Citation
“…In addition, recent studies in adjacent regions of the LIS also included a GIA correction (Norris et al, 2022;Reyes et al, 2022), and, hence, to ensure comparability with these datasets, we apply a correction for GIA-related changes to our dataset as well. The previously mentioned changes in atmospheric conditions following deglaciation work against the impact of GIA on calculated exposure ages, but the impact on exposure ages is likely an order of magnitude lower than that of GIA-induced impacts (Staiger et al, 2007;Cuzzone et al, 2016;Ullman et al, 2016;Dulfer et al, 2021).…”
Section: Exposure Age Calculationmentioning
confidence: 98%
“…As most of the exposure ages postdate the LGM, the influence of katabatic winds and other atmospheric dynamics changes associated with the LIS and CIS ice sheets would have been brief and therefore limited (Staiger et al, 2007). Previous studies that have investigated the impact of changes in atmospheric mass distribution have found that it results in a younger exposure age calculation, but the impact is minimal (∼ 4 % of the GIA correction, Cuzzone et al, 2016; 1 %-5 % of the GIA correction, Ullman et al, 2016; ∼ 1 % of the GIA correction, Dulfer et al, 2021). Coupled with the absence of any model at a suitable resolution, we choose not to make corrections for changes in the atmosphere.…”
Section: Exposure Age Calculationmentioning
confidence: 99%